Preparation and in-vivo evaluation of dimenhydrinate buccal mucoadhesive films with enhanced bioavailability. (2nd June 2016) - Yildiz Pekoz, Ayca; Sedef Erdal, Meryem; Okyar, Alper; Ocak, Meltem; Tekeli, Fatma; Kaptan, Engin; Sagirli, Olcay; Araman, Ahmet
Abstract: Dimenhydrinate (DMH)-loaded buccal bioadhesive films for the prevention and treatment of motion sickness were prepared and optimized. This study examines the rate of drug release from the films for prolonged periods of time to reduce or limit the frequency of DMH administration. Based on preliminary studies using various polymers and concentrations, hydroxyethylcellulose (2.5, 3.0, and 3.2%), and xanthan gum (2.8%) were chosen as matrix polymers. The films were analyzed with respect to their mechanical, physicochemical, bioadhesive, swelling, and in-vitro release properties. In in-vivo pharmacokinetic studies, xanthan gum-based DMH buccal film was associated with significantly increased DMH plasma levels between 1 h and 5 h after DMH dosing when compared with an oral drug solution. The area under the curve AUC0–7 h value of the mucoadhesive buccal film was two-fold higher than the oral DMH solution. Histological analysis revealed that DMH films cause mild morphological and inflammatory changes in rabbit buccal mucosa. The DMH buccal film is effective for approximately 7 h, thus representing an option for single-dose antiemetic therapy. This dosage regimen could be particularly beneficial for chain travelers who travel for long periods of time.